A Necessidade de um refúgio: Transformação da casa de Aldarete - Francisco José Pádua Dias Pereira (2021)
This dissertation focuses on Antón Capitel, one of the "most interesting and complex architectural composition themes" - Rehabilitation. This theme's inherent difficulty is associated with searching for a coherent and balanced solution between apparently paradoxical concepts: permanence and transformation, tradition and innovation, past and present, valuing pre-existence and the need to adapt to contemporary demands. The policy of conserving human evolution's testimonies has been changing over time, from the most remote times to our days, depending on the culture and the geographical place. From this point of view, the intention to prolong a material heritage's life has always relied on recognizing its values and meanings, whether or not they legitimized its future. Hence there is an unmeasurable list of works that have not survived until then, vulnerable either to vandalism, harmful re-use or even to the natural effects of degradation. The inherent problem of how to intervene in the pre-existing context, in the case of a vernacular house inserted in the municipality of Peso da Régua, it motivates the construction of a theoretical narrative that helps the exercise of project. Based on an analytical and reflexive contextualization of how it has been done over time and on an in-depth knowledge of the object's circumstances and conditioning factors to intervene and find an adequate project solution. In the absence of a universal theory of action, the circumstances underlying each intervention will be different. It is up to the architect "to have the sensitivity, through knowledge of pre-existence, to make a synthesis between the past and the present. They are thus adding new meanings and utilities to the existing, without destroying or nullifying it". Thus, the architect walks on the razor's edge between historicist pastiche and contemporary exaltation. Running the risk, in the first case, of freezing the architecture, to integrate into a museum or to transform into a museum piece it, making it unsuited to contemporary demands, and, in the second, of the values introduced annulling the nature and documentary character of the work itself.